Problems of freshmen students adapt to learning in higher education (Pedagogy of Higher and Secondary Education, 2012)
Balahtar V. Problems of freshmen students adapt to learning in higher education.The article was concerned with the problem of student’s adaptation and characterized the major factors. Has been investigated the state of adaptation of the first-year students to the learning environment in the school for higher education.
Keywords: adaptation; first-year student; personality; group; device; interaction